Almost Periodic Solutions of Partial Differential Equations with Delay - Henriquez-Miranda, H (Springer Verlag, 2015)
In this paper we study the existence of almost periodic solutions for linear retarded functional differential equations with finite delay and values in a Banach space. We relate the existence of almost periodic solutions with the stabilization of distributed control systems. We apply our results to transport models and to the wave equation. © 2015, Henríquez et al.; licensee Springer.